Student Worksheet of Light and Optics for STEM-Based Problem-Based Learning: Critical Thinking Skills Perspective - Fifi Suaidatur Rofik; Habiddin Habiddin; Muhammad Fajar Marsuki (PT Ahan Group Publisher, 2025)
This study investigates the effectiveness of student worksheets in an integrated Problem-Based Learning model using the STEM approach on light and optical materials towards improving the critical thinking skills of eighth-grade students of SMPN 1 Kepanjen. Student worksheets were developed using the 4D model of Thiagarajan (1974). This study was a pre-experimental design using a one-group pretest-posttest. The research instruments were critical thinking ability tests and questionnaires. The paired sample t-test results showed a significant difference in students' critical thinking skills before and after learning on the STEM-based Problem-Based Learning student worksheet. Supported by an N-Gain score of 48.14%, the developed students' worksheet effectively improves students' critical thinking skills.